Návrh na rozšíření gastronomických služeb firmy Imperial Catering - Sichler, Radim (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Tato diplomová práce se zabývá tvorbou návrhu na rozšíření gastronomických služeb firmy IMPERIAL CATERING, s.r.o. Práce popisuje a analyzuje oblasti gastronomie a tržního oboru podnikání, ve kterém se firma pohybuje. Snaží se najít možnosti zlepšení poskytovaných služeb a tím docílit zlepšení současné pozice firmy na trhu.

This study deals with creating suggestions for extension of gastronomic services in the IMPERIAL CATERING, company. It describes and analyses gastronomy and the business environment in which company operates. It also tries to find ways of improving services and that way to establish and improve the company’s position on the market.
Suggestions for extension of gastronomic services in the Imperial Catering company
Keywords: podnikatelský plán; marketingový mix; catering; gastronomie; business plan; marketing mix; catering; gastronomy